Fabrication of NiO–ZnO-modified g-C3N4 hierarchical composites for high-performance supercapacitors. (August 2020) - Chen, Xiaoyan; Wang, Xinzhen; Liu, Fengjun; Song, Xiaojie; Cui, Hongzhi
Abstract: In this work, NiO and ZnO co-modified g-C3 N4 (NiO–ZnO@g-C3 N4 ) hierarchical nanocomposite was synthesized using a simple hydrothermal method and used as a high-performance supercapacitor electrode. NiO–ZnO@g-C3 N4 consisted of NiO nanoparticles, ZnO nanoparticles, and g-C3 N4 nanosheets, in which the g-C3 N4 nanosheets served as the matrix for the attachment of NiO and ZnO nanoparticles. Electrochemical tests showed that NiO–ZnO@g-C3 N4 displayed an improved electrochemical performance compared with pure NiO. The specific capacitance of NiO–ZnO@g-C3 N4 was 726.7 F g −1 at a current density of 0.5 A g −1, which was about 2.1 times higher than that of pure NiO (346.2 F g −1 ). The capacitance remained at 78% after 1000 cycles at 5 A g −1, demonstrating the good cycle performance of NiO–ZnO@g-C3 N4 . Moreover, the energy density of NiO–ZnO@g-C3 N4 reached 7.91 Wh kg −1 at a power density of 160 W kg −1 . The enhanced performance of the NiO–ZnO@g-C3 N4 hierarchical nanocomposite was attributed to its unique structure and composition. Graphical abstract: Image 1 Highlights: NiO and ZnO co-modified g-C3 N4 hierarchical nanocomposite was synthesized. g-C3 N4 is a promising material for supercapacitors can be easily prepared. The specific capacitance of NiO–ZnO@g-C3 N4 was 726.7 F g −1 at 0.5 A g −1 . It delivers a good cycle stability.